Encapsulation and removal of aniline by di-cyclohexanocucurbit[6]uril. (20th December 2018) - Zhang, Mingli; Shi, Hao; Meng, Di; Chen, Kai; Lin, Rui-Lian; Sun, Wen-Qi; Liu, Jing-Xin
Abstract : The binding behaviors of Cy2Q[6] and Cy6Q[6] with aniline, p -methylaniline, and p -phenyldiamine were investigated by various techniques, which suggests that Cy2Q[6] is a promising candidate for aniline removal because of its oval cavity. Abstract : This research investigated the binding behaviors of hosts symmetrical di-cyclohexanocucurbit[6]uril (Cy2Q[6]) and hexa-cyclohexanocucurbit[6]uril (Cy6Q[6]) with guests aniline, p -methylaniline, and p -phenyldiamine. 1 H NMR data suggest that hosts Cy2Q[6] and Cy6Q[6] can accommodate all guests to form stable inclusion complexes in aqueous solution. X-ray crystallography provides unequivocal evidence that Cy2Q[6] forms inclusion complexes in the solid state with all guests, in which the aromatic rings of the guests are encapsulated. Most importantly, entrapment tests and thermogravimetric analyses show that the Cy2Q[6] host possesses higher removal efficiency for aniline than the Cy6Q[6] host. All results show that the Cy2Q[6] host is more suitable for the recognition and encapsulation of the studied guests than the Cy6Q[6] host because its size and shape are more complementary to the aromatic rings of the guests. Our study suggests the potential utility of Cy2Q[6] as an adsorbent for aniline removal.